Nosocomial E. Coli Isolated from UTI Identified Using DNA Markers Based on PCR and Pathogenic Markers - Shler Ali Khorsheed (National Journal of Medical Research)
Background: Urinary tract infections (UTIs) are among the most common bacterial infections, with Escherichia coli (E. coli) being the leading causative agent. The increasing resistance of E. coli to commonly used antibiotics, including β-lactam antibiotics, poses a significant clinical challenge. Understanding antimicrobial resistance patterns and genetic diversity among E. coli isolates is essential for effective treatment and infection control. This study aimed to determine the prevalence of E. coli in UTI cases, assess its resistance to multiple antibiotics, evaluate β-lactamase and extended-spectrum beta-lactamase (ESBL) production, and analyze genetic diversity using molecular techniques.